5(2x-4)+7=12+3(2x+1)

Simple and best practice solution for 5(2x-4)+7=12+3(2x+1) equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 5(2x-4)+7=12+3(2x+1) equation:


Simplifying
5(2x + -4) + 7 = 12 + 3(2x + 1)

Reorder the terms:
5(-4 + 2x) + 7 = 12 + 3(2x + 1)
(-4 * 5 + 2x * 5) + 7 = 12 + 3(2x + 1)
(-20 + 10x) + 7 = 12 + 3(2x + 1)

Reorder the terms:
-20 + 7 + 10x = 12 + 3(2x + 1)

Combine like terms: -20 + 7 = -13
-13 + 10x = 12 + 3(2x + 1)

Reorder the terms:
-13 + 10x = 12 + 3(1 + 2x)
-13 + 10x = 12 + (1 * 3 + 2x * 3)
-13 + 10x = 12 + (3 + 6x)

Combine like terms: 12 + 3 = 15
-13 + 10x = 15 + 6x

Solving
-13 + 10x = 15 + 6x

Solving for variable 'x'.

Move all terms containing x to the left, all other terms to the right.

Add '-6x' to each side of the equation.
-13 + 10x + -6x = 15 + 6x + -6x

Combine like terms: 10x + -6x = 4x
-13 + 4x = 15 + 6x + -6x

Combine like terms: 6x + -6x = 0
-13 + 4x = 15 + 0
-13 + 4x = 15

Add '13' to each side of the equation.
-13 + 13 + 4x = 15 + 13

Combine like terms: -13 + 13 = 0
0 + 4x = 15 + 13
4x = 15 + 13

Combine like terms: 15 + 13 = 28
4x = 28

Divide each side by '4'.
x = 7

Simplifying
x = 7

See similar equations:

| 816=24(v+12) | | 3)x-y)/5(2x/3y) | | -7(1+5x)=7(x+5) | | 120/350 | | 5y^2+4+1y=4 | | 2m^3+2m^2-24m= | | f(x)=164-16x | | W-15=0 | | 3/7•14 | | 48+54r=-15r | | 6r-18=-32+4r | | -12/17y=13 | | -15x-8-(-25)+18x=0 | | 4.375=28/v | | 5x-20+16x+16=6x+6+5x+50 | | 3x+3=1/81 | | 260h+18=240h+22 | | 3z-19=-11+z | | 2+.5= | | 4x+80=-6x-8 | | sqrt(3x+12)+sqrt(3x-8)=10 | | sinx=sqrt3/2 | | 8d-32+24d-64=40 | | x^4-x^2+3=0 | | 2x-5whenx=12 | | -2x-1=-4 | | a/6=25 | | 24-12-(-14)=x | | P-8=12-3p | | 4p+1000000=12600000 | | ln(x+1)+ln(x+1)=2 | | g-9=-2g+6 |

Equations solver categories